Linear, third order nonlinear and optical limiting studies on MZO/FTO thin film system fabricated by spin coating technique for electro-optic applications. Issue 22 (10th September 2018) - Shkir, Mohd.; Arif, Mohd.; Ganesh, Vanga; Manthrammel, Mohamed A.; Singh, Arun; Maidur, Shivaraj R.; Patil, Parutagouda Shankaragouda; Yahia, Ibrahim S.; Algarni, Hamed; AlFaify, Salem
Abstract: Abstract : Herein, we report the detailed optoelectronic characteristics of low cost fabricated pristine and 1, 5, 10, and 15 wt% Mg-doped ZnO films on the FTO substrate (MZO/FTO) through the spin coating technique. High crystallinity and single phase of the film were confirmed by X-ray diffraction investigation. The average crystallite size was in the range of 46–78 nm. Homogeneous distribution of Mg doping in ZnO was approved by elemental mapping analysis. The fiber-like surface morphology was confirmed by the scanning electron microscopy analysis. Optical transparency was observed in the range of 40–80% for the fabricated films. The optical band gaps for direct and indirect transitions obtained from Tauc's relation are in the range of 3.103–3.283 eV and 2.423–2.968 eV, respectively. It is also observed that the energy gap of MZO films decreases with an increase in Mg doping from 1 to 15%. The respective stable values of absorption and refractive indices are obtained in the range of ∼0.036–0.088 and ∼1.71–2.1. The linear and nonlinear optical susceptibilities as well as the nonlinear refractive index values were calculated. Additionally, Z-scan measurement was carried out at 532 nm wavelength. The nonlinear absorption coefficient and the imaginary part of third-order nonlinear susceptibility were estimated and corresponding values are obtained in the range of 0.35–123 (×10 −5 ) cm/W and 0.084–29.7 (×10 −8 ) e.s.u., respectively. Moreover, the optical limiting threshold values were obtained in the range of 2.57–6.34 kJ/cm 2 . The MZO/FTO films are showing strong optical limiting behavior compared to pristine. The output results suggest that MZO films are better contenders for optoelectronic applications.